Analysis of The Influence of Customer Perceived Benefit, Ease of Use and Sales Promotion on The Decision to Use Digital Wallets for Shopeepay Customers - Frans Sudirjo; Helmy Syamsuri; Ainil Mardiah; Agung Widarman; Yulia Novita (Jurnal Sistim Informasi dan Teknologi, 2023)
This study looks at how factors like convenience, utility, and sales promotion affect people's decisions to use multiple e-wallets at once. Because the respondents surveyed utilize e-wallets, and because it is impossible to anticipate how many users there will be over time, this study uses an infinite population. Purposive sampling was employed to choose the sample for this study. Thus, the researcher decided that 250 respondents who had used e-wallets would make up the sample. Researchers use questionnaires to gather data. The questionnaire was disseminated by the researchers via social media. Multiple linear regression analysis with the aid of SPSS software is the data analysis technique used in this study. T-statistics are applied to test this proposition. The choice to use an e-wallet is significantly influenced by sales promotions. Choosing to use an e-wallet is strongly influenced by convenience. The choice to use an e-wallet is significantly influenced by its usability. The decision to utilize an e-wallet is heavily influenced by convenience, usefulness, and sales promotion all at once.